Methodological Features of The Application of Unconventional Means of General Physical Training in The Teaching and Training Process of Young Greco-Risk Style Wrestlers - Tashnazarov Jasur Yuldashevich (Zien Journals, 2022)
This empirical material reveals the content of the systems of "crossfit" and yoga, shows the rationality of the redistribution of the means of the volume of the general physical training of young wrestlers of the Greco-Roman style in favor of using a greater percentage of the exercise complexes of the "crossfit" system, in comparison with the traditional means of the educational - training process.
Keywords: Physical characteristics; physical fitness; training process; competition